Quantum higher-order Fourier analysis and the Clifford hierarchy - Kaifeng Bu; Weichen Gu; Arthur Jaffe (Proceedings of the National Academy of Sciences, 2025)
We propose a mathematical framework that we call quantum, higher-order Fourier analysis. This generalizes the classical theory of higher-order Fourier analysis, which led to many recent advances in number theory and combinatorics. We define a family of “quantum measures” on linear transformations on a Hilbert space, that reduce in the case of diagonal matrices to the uniformity norms introduced by Timothy Gowers. We show that our quantum measures and our related theory of quantum higher-order Fourier analysis characterize the Clifford hierarchy, an important notion of complexity in quantum computation. In particular, we give a necessary and sufficient analytic condition that a unitary is an element of the k th level of the Clifford hierarchy.